Resource Sharing and Allocation in Cloud Via Social Networks - Florence, S; Shyamala Kumari, C; Prema, K; Leema Priyadarshini, L (International Journal of Engineering and Technology, 2018)
Social network plays a major role in communication and interaction of the people. Nowadays, cloud computing is the emerging technology in the field of Information Technology. The allocation and sharing of resources can be possible in an innovative way, by combining the social networks processes and cloud computing concepts. In the social network cloud, based on the friendâ€™s relationship strength the resources can be provided from one friend to another. Based on the clustering techniques the similar type of friends will be grouped and the resources will be allocated. The resource providers recommend the virtualized containers on their devices itself. For efficient allocation of resources the effective allocation algorithms are used. Based on the type of relationship they had, the relationship based access control mechanisms are provided.Â Â